(3GdQSGdI GdMSGHjI aj GdCYeGd GdCaGbjIs - (3fLe GdOjf CHh YHO Gddg eMeO Hf eMeO GdeUQjs ((3CMeO Hf GHQGgje GdSWMi s)
(3ChdgG (B:s
(3gPg GdQSGdI JCdja GdTjN fLe GdOjf CHj YHO Gddg eMeO Hf eMeO GdeUQi JTJed Ydi afhf ef Yde GdejbGJ GdHGH GdChd ai eYQaI OQLI GdTeS ef HQLgG s
(3BNQgG (B:s
(3ef MSH ZGjJg aeG Hbi agh MSH GQJaGY afXQ GdeOGQ hPdc dGjecf EdG ai GdCLRGA GdehGabg dLgI GdYQV hGddg GYde JeJ HMeO Gddg JYGdi hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdGeHQhRjGfG s
Keywords: (3Gdadcs